THE GEOMETRY OF THE SIMPLEX METHOD AND HIS APPLICATIONS USING MATLAB® - Raffo Lecca, Eduardo (2007)
The article review concepts of computacional geometry apply to simplex methods using MATLAB®. Do it programming linear PL, a feasible solution is a vector who specify all restrictions, incluides that sign. The work check concepts of computacional geometry, the simplex method, and show the maner to apply graph form one problem PL. To include meta files(of MATLAB, version 7.0). Finally to argue two case of a problem PL.